Electrophoresis of an ellipsoid along the axis of a cylindrical pore effect of a charged boundary - Tseng, Shiojenn (Langmuir : the ACS journal of surfaces and colloids, 2008)
The influence of a charged boundary on the electrophoretic behavior of a particle is investigated by considering the electrophoresis of a nonconducting ellipsoid along the axis of a cylindrical pore at the level of the linear Poisson-Boltzmann equation ignoring the polarization effect. The problem considered simulates the electrophoresis conducted in a narrow space such as capillary electrophoresis and electrophoresis through a porous medium. Here, because the effect of electroosmotic flow can be important the electrophoretic behavior is much more complicated than that for the case where a boundary is uncharged. The influences of the thickness of double layer, the aspect ratio of an ellipsoid, the relative radius of a pore, and the charge conditions on the ellipsoid and pore surfaces on the mobility of the ellipsoid are discussed. Several interesting but nonintuitive electrophoretic behaviors are observed